Where do Critical Pedagogy and Language Needs Analysis meet? English as an Additional Language for Adult Refugees and Mi-grants in Greece: A Case Study - Christina Maligkoudi; Anna Mouti; Eleni Triantafyllou (National Research University Higher School of Economics, 2023)
Background. Language classes organized for adult refugees and migrants are heterogeneous. Students in these educational settings differ across a number of various aspects, including language competences, educational background and levels of literacy. Seen through the Critical Pedagogy lens language is considered not simply as a means to express or communicate, but as a product constructed by the ways language learners recognise themselves, their social surroundings, their histories, and their potentialities for the future. Purpose. The purpose of our study is to unfold and identify the language needs of a specific group of migrants learners learning English as an additional language in Greece, where English is not the dominant language. We will try to focus and analyse language needs through the critical pedagogy lens and thus make the whole procedure an empowerment tools for the adult refugees and migrants. Method. As a case study, this study follows a qualitative research design. Τhis small-scale study focuses on a specific target group of language learners and their needs and attitudes towards learning. Class observations, field notes, interviews with the participants and questionnaires with open-ended questions were used as main methodological tools. Results. The present article examines the needs of a group of immigrant adult learners attending English language classes at a non-formal educational setting located in Greece. The participants come from diverse ethnic and linguistic backgrounds and the majority of them speak Greek fluently since they have resided in Greece for a long time. A focal point throughout the process was students' greater involvement in the learning procedure and decision-making processes regarding the content and the presentation of the educational material. Conclusion. Although the systematic needs analysis revealed that the reasons for participation and competence levels among participants varied a lot, a common goal for everyone was achieving oral fluency in the target language. Moreover, the results of this attempt were expressed n terms of learners' contributions, willingness to share their stories, even to talk about difficulties they met and caring about their classmates' stories. Thus, we suggest that the incorporation of personal experience in the learning process, not only functions as a link between students and language but also a process for team bonding and motivation.